2010
DOI: 10.1007/s00423-010-0708-0
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemoradiotherapy for rectal carcinoma: effects on anastomotic leak rate and postoperative bladder dysfunction after non-emergency sphincter-preserving anterior rectal resection

Abstract: Neoadjuvant chemoradiotherapy for rectal carcinoma does not increase the risk for anastomotic leakage or postoperative bladder dysfunction after curatively intended sphincter-preserving rectal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
2
28
0
4
Order By: Relevance
“…We postulated that radiation might have adverse effects on the autonomic nerves and consequently result in bladder dysfunction. However, Garlipp et al [26] demonstrated that preoperative CRT was not a risk factor for bladder dysfunction after undergoing a sphincter preserving rectal resection. The relationship between preoperative CRT and bladder dysfunction has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…We postulated that radiation might have adverse effects on the autonomic nerves and consequently result in bladder dysfunction. However, Garlipp et al [26] demonstrated that preoperative CRT was not a risk factor for bladder dysfunction after undergoing a sphincter preserving rectal resection. The relationship between preoperative CRT and bladder dysfunction has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller subset has also looked into the potential implications on long-term bladder as well as sexual function; however, the issue also becomes more difficult to analyze due to the need for intraoperative preservation of the autonomic nerve plexuses [64]. Despite the large number of randomized trials that have investigated the role of various regimens of neoadjuvant therapy, few have done so with a standardized TME dissection protocol for participating surgeons.…”
Section: Surgery-related Outcomes Following Neoadjuvant Therapy: Funcmentioning
confidence: 99%
“…Therefore, these locations of GI anastomoses are the most studied. Although some have reported no increase in anastomotic leak in colorectal surgery following chemoradiation therapy, 51 others have demonstrated that there is evidence that preoperative chemotherapy increases the risk of anastomotic leak in colorectal surgery. 1,52 At the same time, neoadjuvant chemotherapy has not been shown to increase anastomotic leak rate in esophageal surgery.…”
Section: Steroids/immune Modulatorsmentioning
confidence: 99%